Oil palm shell lightweight concrete as a ductile material - Shafigh, Payam; Mahmud, Hilmi; Jumaat, Mohd Zamin (Elsevier, 2012)
Crushed large oil palm shell (OPS) was used as a coarse aggregate in four different concrete mixtures. The stress-strain behavior and modulus of elasticity of OPS concrete were investigated and compared to granite normal weight concrete (NWC) and expanded clay lightweight concrete (LWC). The stress-strain curve of the OPS concrete showed that this type of LWC, in contrast to many types of structural LWC, is a ductile material. The highest E value of about 18.4. GPa was achieved in this study, which is significantly higher than previous studies. It was found that the E value of crushed OPS LWC was approximately 53 of the control NWC, which is approximately twice that of the uncrushed OPS concrete reported in the literature.